Ameloblastic Fibrosarcoma arising in the mandible - Marcelo Marcucci; Karina Cecília Panelli Santos; Juliane Pirágine Araújo; Décio Santos Pinto Junior; Jefferson Xavier Oliveira (Editorial Ciencias Médicas, 2016)
Introduction: Ameloblastic Fibrosarcoma (AFS) is a rare odontogenic neoplasm and is considered the malignant counterpart of Ameloblastic Fibroma. The diagnosis is made by histopathological and immunohistochemical evaluation, since the epithelial component remains benign and the mesenchymal component becomes malignant. Until 2012, only 72 cases were published in English-literature. Objective: This article presents a case of intraoral mass at the posterior mandible of a 23 year-old female patient. Case presentation: Panoramic radiography showed a multilocular radiolucent lesion with ill-defined borders and tooth involvement. The mandibular canal presented loss of architecture also. The computed tomography (CT) images (bone window) showed hypodense lesion leading to expansion, tapering and irregular destruction of cortical, and tooth involvement. Incisional biopsy was performed for histopathological evaluation. The results revealed a mixed lesion with epithelial and mesenchymal cellular proliferation. At immunohistochemical analysis, the mesenchymal portion was vimentin positive and the epithelial component was positive for cytokeratin AE1-AE3. It also showed p53 intense labeling in all tumorous cells. The final diagnosis was ameloblastic fibrosarcoma. The lesion was surgically excised with clear margins. Conclusion: The radiographic appearance, even imperative for treatment planning, poorly contributed to final diagnosis, which was reached by histopathological and immunohistochemical evaluations. The treatment is still controversial, without a definition regarding chemotherapy and radiotherapy as coadjutant treatment.